IMPACT OF HOTEL, RESTAURANT AND ENTERTAINMENT TAXES ON LOCAL OWN REVENUE IN WEST JAVA - Mutia Nursyahbani Anwar; Dian Octaviani (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This Study aims to analyze the effect of hotel tax, restaurant tax and entertainment tax on local own revenue. This study uses data sourced from the Directorate General of Fiscal Balance (DJPK) with secondary data from 2016-2019. The analytical method used is the panel data regression method with the help of the eveiws 9 application. The results of this study show that hotel tax, restaurant tax, and entertainment tax individually and jointly have a positive and significant effect on local own revenue.